Online registry of neonatal necrotising enterocolitis in Shenzhen: protocol for a multicentre, prospective, open, observational cohort study - Jun Chen; Cheng Chen; Hong Tang; Fang Lin; Dong Liu; Zhihua Chen; Xin Guo; Guanming Li; Xiaodong Li; Jinxing Feng; Qianshen Zhang; Lei Dou; et al. (BMJ Open)
Introduction Necrotising enterocolitis (NEC) of the intestine of preterm infants leads to the risk of abdominal surgery, short bowel syndrome, neurodevelopmental disorders and death. Although the risks of NEC and its complications have been recognised in many countries, few countries have established NEC-specific registries to continuously monitor its aetiology and prognosis. In China, the understanding of risk factors and prognosis of NEC is incomplete, characterised by a lack of evidence from prospective and multicentre studies. Therefore, we designed a multicentre, prospective, open observational cohort study with the aim of investigating the risk factors and prognosis of NEC in a real-world setting in Shenzhen, Guangdong Province, by constructing an online registry of children with NEC and a bank of biospecimens.Methods This is a prospective, multicentre, open observational cohort study. From June 2024 to June 2028, more than 600 patients with NEC from 15 tertiary hospitals in Shenzhen, Guangdong Province, will be enrolled in the study. By constructing an online registry for NEC, clinical data will be collected during the prenatal and hospitalisation periods. Prospectively, biospecimens will be collected during the period of suspected NEC, at the time of confirmed NEC, and at the time of confirmed severe NEC, and filed in the online registry system. Follow-up data will include postdischarge healthcare needs, growth patterns measures, eye or vision examinations, cranial MRI findings, brainstem auditory evoked potentials or automated auditory brainstem responses, and the Chinese Griffith Developmental Scale at corrected age 18–24 months. Follow-up results were likewise recorded in an online registry system. Hospitalisation outcomes, including severe NEC, somatic growth and survival status, will be collected at discharge. Follow-up outcomes will include loss to visit, survival status, somatic growth measures and severe neurodevelopmental deficits at corrected age 18–24 months. This study will enhance our overall understanding of the risk factors and outcomes of NEC, ultimately helping to reduce the incidence of neonatal NEC and its poor prognosis.Ethics and dissemination Our programme has received approval from the Ethics Committee for Scientific Research Projects of the Longgang District Maternity & Child Healthcare Hospital in Shenzhen City (ethics approval number: LGFYKYXMLL-2024-47-01). We anticipate presenting our findings at various national conferences and submitting them to peer-reviewed paediatrics journals.Trial registration number ChiCTR2400085043.